PENGARUH MODEL LEARNING CYCLE 5E BERBANTUANMEDIA VIDEO TERHADAP KETERAMPILAN MENULIS ARTIKEL SISWA KELAS XI SMA NEGERI 1 PAGADEN - Tanti Oktaviani; Desti Kusmayanti; Irpan Maulana (Universitas Hamzanwadi, 2026)
This study looks at how using the 5E learning cycle along with video media affects the article writing skills of eleventh-grade students at SMA Negeri 1 Pagaden. It focuses on students' ability to create relevant content, organize their writing, use proper spelling and punctuation, apply good language features, and make clear sentences. The research uses a quantitative method with a quasi-experimental setup, involving 68 students split into two groups: one that used the 5E cycle with videos and a control group that didn't. Students were tested by writing articles, and their scores were compared before and after the intervention. The experimental group's scores went up from an average of 34.73 in the pretest to 76.61 in the posttest, while the control group's scores increased from 34.88 to 53.23. The experimental group had an N-Gain score of 0.64, which is considered moderate, compared to the control group's 0.28, which is low. A T-Test showed a very revealing that the difference between the two groups is statistically significant, with a p-value of 0.000. These results suggest that using the 5E learning cycle with video media helps improve students' writing performance by making them more involved, better at organizing their ideas, and more accurate with language.